Senegal : Poverty Reduction Strategy Paper: Joint Staff Advisory Note on the National Strategy for Economic and Social Development. (IMF Staff Country Reports; Country Report ;, 2013)
The joint staff Advisory Note on Senegal's Poverty Reduction Strategy Paper reviews policies and strategies required to push forward the authority's agenda for high, sustained, and inclusive growth and poverty reduction. The private sector is recognized as the main engine of growth in the Senegalese economy. The strategy is clearly focused on improving the investment climate, fostering entrepreneurship, and facilitating access to financial services for small and medium-sized enterprises, and consolidating support institutions. Senegal's water and sanitation sector is one of the most developed in sub-Saharan Africa. The urban water Millennium Development Goal has been achieved, with access for 98 percent of the urban population, and the goal for rural water access is within reach.